Olefins and Vinyl Polar Monomers: Bridging the Gap for Next Generation Materials. Issue 36 (1st August 2019) - Keyes, Anthony; Basbug Alhan, Hatice E.; Ordonez, Estela; Ha, Uyen; Beezer, Dain B.; Dau, Huong; Liu, Yu‐Sheng; Tsogtgerel, Enkhjargal; Jones, Glen R.; Harth, Eva
Abstract: The inherent differences in reactivity between activated and non‐activated alkenes prevents copolymerization using established polymer synthesis techniques. Research over the past 20 years has greatly advanced the copolymerization of polar vinyl monomers and olefins. This Review highlights the challenges associated with conventional polymerization systems and evaluates the most relevant methods which have been developed to "bridge the gap" between polar vinyl monomers and olefins. We discuss advancements in heteroatom tolerant coordination–insertion polymerizations, methods of controlling radical polymerizations to incorporate olefinic monomers, as well as combined approaches employing sequential polymerizations. Finally, we discuss state‐of‐the‐art stimuli‐responsive systems capable of facile switching between catalytic pathways and provide an outlook towards applications in which tailored copolymers are ideally suited. Abstract : Polymers for next generation materials : Functionalized polyolefins are obtained through a variety of synthetic platforms, including insertion–coordination and radical polymerization techniques. Merging these two approaches has led to the development of block and graft copolymers with olefinic and polar segments. Recent advances have allowed for a one‐pot synthesis of functionalized polyolefins using stimuli‐responsive catalysts.